The role of the RHOA/ROCK pathway in the regulation of myometrial stages throughout pregnancyAJOG Global Reports at a Glance - Jorge A. Carvajal, MD, PhD; Jose Galaz, MD; Sofía Villagrán, MD; Rocío Astudillo, MD; Liliana Garmendia, MSc; Ana María Delpiano, MSc (Elsevier, 2024)
Background: Controlling uterine contractile activity is essential to regulate the duration of pregnancy. During most of the pregnancy, the uterus does not contract (i.e., myometrial quiescence). The myometrium recovers its contractile phenotype at around 36 weeks (i.e., myometrial activation) through several mechanisms. The RHOA/ROCK pathway plays a vital role in facilitating muscular contractions by calcium sensitization in humans. Yet, the role of this pathway during different myometrial stages, including quiescence, has not been elucidated. Objective: we aimed to study the role of the RHOA/ROCK pathway in the regulation of the different myometrial stages throughout pregnancy. Specifically, we hypothesized that the inhibition of the components of the RHOA/ROCK pathway play an important role in maintaining uterine quiescence. Study design: Myometrial samples were obtained from pregnant individuals who underwent cesarean section. Pregnant individuals who delivered preterm without labor (myometrial quiescence), preterm with labor (nonphysiological myometrial stimulation), term not in labor (activation), and term in labor (physiological myometrial stimulation) were included. The mRNA and protein expression of RHOA, ROCK I, ROCK II, RND1-3, and ROCK activity through pMYTP1 were evaluated. Results: We found that the human myometrium constitutively expressed RHOA/ROCK pathway components throughout pregnancy. No changes in the components of the RHOA/ROCK pathway were found during quiescence. Moreover, the RHOA protein and ROCK activity increased in the myometrium during labor, supporting the hypothesis that this pathway participates in maintaining the contractile activity of the myometrium. This study provides insight into the role of the RHOA/ROCK pathway in controlling myometrial contractile activity during pregnancy.